Предмет: Алгебра, автор: aleop4

Решите пожалуйста!!.....

Приложения:

Ответы

Автор ответа: Universalka
0

1)\frac{3x^{-2} }{2-x^{-2}}- \frac{3x^{-2} }{2+x^{-2}}=\frac{3x^{-2}*(2+x^{-2})-3x^{-2}*(2-x^{-2})}{(2-x^{-2})(2+x^{-2})}=\frac{6x^{-2}+3x^{-4}-6x^{-2}+3x^{-4}}{4-x^{-4}}=\\\\=\frac{6x^{-4}}{4-x^{-4}} \\\\x=1\\\\\frac{6*1^{-4} }{4-1^{-4}}=\frac{6}{4-1} =\frac{6}{3}=2\\\\Otvet:\boxed2

2)\frac{2x^{-1}-y^{-1}}{2x^{-1}+y^{-1}}\\\\x=2 ; \ y=1\\\\\frac{2*2^{-1}-1^{-1}}{2*2^{-1}+1^{-1}}=\frac{2*\frac{1}{2}-1}{2*\frac{1}{2} +1}=\frac{1-1}{1+1}=\frac{0}{2}=0\\\\Otvet:\boxed0

Похожие вопросы
Предмет: Қазақ тiлi, автор: nikitastr0071
Предмет: Геометрия, автор: ппмв